2019
DOI: 10.1002/jsid.848
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming latency with motion prediction in directional autostereoscopic displays

Abstract: Imaging delivering to correct retina assisted with tracking technique is a common practice for autostereoscopic displays with stereo two‐view data format. Due to various latencies produced in camera buffering, computer processing, data transmission, and illumination refreshing, delayed image delivery will give rise to a substantial degradation of the 3D display experience. This is particularly obvious for directional backlight 3D displays where significant flickering is resulted as a result of the inherent lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…With this technique, two front cameras were used to determine the exact location of the retina, and the test pictures or videos were sent to the subject's eyes to detect any possible movement, hence enhancing the accuracy of the examination. Furthermore, the eye-tracking technique can be used to instantaneously detect a subject's movement using state-of-the-art eye-tracking technique with motion prediction to produce a flicker-free viewing experience (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…With this technique, two front cameras were used to determine the exact location of the retina, and the test pictures or videos were sent to the subject's eyes to detect any possible movement, hence enhancing the accuracy of the examination. Furthermore, the eye-tracking technique can be used to instantaneously detect a subject's movement using state-of-the-art eye-tracking technique with motion prediction to produce a flicker-free viewing experience (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Even though this study predicted 6DoF motion among VR users, the data collected from the sample did not explore the worst-case scenarios for when the user performs abrupt movements while playing VR games, focusing instead on scenery-based VR apps. Another limitation in this study was their use of 60 window time data (666 ms) to predict only 11 ms in the future, which is not practical since recent VR-HMDs still have latency between 43 and 85 ms [5][6][7][8][9].…”
Section: Related Studiesmentioning
confidence: 99%
“…These accumulated delays can be reduced but never eliminated since they come from the hardware and software requirements. Moreover, recent literature from 2019-2020 showed that current VR-HMD still possesses an MTP latency varying between 43 and 85 ms [5][6][7][8][9]. Using an Acer device, R. Gruen et al (2020) tested the latency on four different VR devices: Oculus Rift S, Valve Index, Oculus Quest, and Prim.…”
Section: Introductionmentioning
confidence: 99%
“…26 The crosstalk can cause visual fatigue and even physiological discomfort, which should be controlled to a lowest possible value. To reduce the temporal crosstalk, the screen and the backlight need refreshing synchronously, 26 or the gating time of the backlight in the DBAD system in a refresh cycle is adjusted to 2 ms. 27,28 Two-dimensional (2D) lens array and 2D backlight array may be helpful to control the crosstalk, but it is technically difficult to realize at present. 26 Moreover, the majority of 4, 8 even 16 K panels work in low refresh rate, which are not suitable for temporal shutter scheme.…”
Section: Introductionmentioning
confidence: 99%